Drug treatments for gestational diabetes mellitus: an integrative literature review (Research, Society and Development, 2022)
Gestational diabetes mellitus is a type of diabetes mellitus that affects about 8% of pregnant women with or without diabetes prior to pregnancy in Brazil, and can cause multiple problems in the formation of the fetus throughout pregnancy and for the safety of the pregnant woman, leading to death. This article discusses the treatments based on the use of drugs exposed in the specialized literature, in Portuguese, between 2017 and 2022. The search was made in the scielo, Pubmed and Scopus repositories with the terms " gestational diabetes”, “gestational diabetes”, “gestational diabetes mellitus”, "metformin”," metformin gestational diabetes " published within said time frame and that cite possible drug treatments for the condition studied, being found 10 texts that delve into the central theme of this text. Finally, it is concluded that according to the literature, metformin and insulin therapy remain the best treatments to control gestational diabetes mellitus.